No Association Between Time of Onset of Hearing Loss (Childhood Versus Adulthood) and Self-Reported Hearing Handicap in Adults - Aarhus, Lisa (Am J Audiol, 2015)
PURPOSE: This study examined the association between time of onset of hearing loss (childhood vs. adulthood) and self-reported hearing handicap in adults. METHODS: This is a population-based cohort study of 2,024 adults (mean = 48 years) with hearing loss (binaural pure-tone average 0.5–4 kHz ≥ 20 dB HL) who completed a hearing handicap questionnaire. In childhood, the same persons (N = 2,024) underwent audiometry in a school investigation (at ages 7, 10, and 13 years), in which 129 were diagnosed with sensorineural hearing loss (binaural pure-tone average 0.5–4 kHz ≥ 20 dB HL), whereas 1,895 had normal hearing thresholds. RESULTS: Hearing handicap was measured in adulthood as the sum-score of various speech perception and social impairment items (15 items). The sum-score increased with adult hearing threshold level (p < .001). After adjustment for adult hearing threshold level, hearing aid use, adult age, sex, and socioeconomic status, there was no significant difference in hearing handicap sum-score between the group with childhood-onset hearing loss (n = 129) and the group with adult-onset hearing loss (n = 1,895; p = .882). CONCLUSION: Self-reported hearing handicap in adults increased with hearing threshold level. After adjustment for adult hearing threshold level, this cohort study revealed no significant association between time of onset of hearing loss (childhood vs. adulthood) and self-reported hearing handicap.